Six Heads Are Better Than One? School-Based Decision Making in Rural Kentucky - Patricia J. Kannapel; Beverly D. Moore; Pamelia Coe; Lola Aagard (Journal of Research in Rural Education, 1995)
As a result ofthe Kentucky Education Reform Act of 1990, most schools in Kentucky must implement school-based decision making (SBDM) by 1996. Our study examines the work ofSBDM councils infour rural Kentucky school districts over a 3-year period. We examine the extent to which decisions were shared among the role groups represented on councils, the kinds ofdecisions councils made, and the quality ofcouncil decisions. Findings in all areas are contrasted with research findings about SBDM in urban and suburban settings. We found that, like SBDM in urban and suburban settings, true shared decision making among administrators, teachers, and parents was difficult to achieve. While the rural councils in our study initially dealt with a different set ofissues than urban and suburban councils, they resembled their metropolitan counterparts in that they did not move quickly into issues related to curriculum and instruction. Finally, the quality ofdecisions made by the councils in our study varied: Decisions about hiring principals and budget management generally appeared more likely to lead to school improvement than decisions about discipline and instruction.